The Influence of Solvent and Extraction Time on Yield and Chemical Selectivity of Cuticular Waxes from Quercus suber Leaves - Simões, Rita (2022)
The cuticular lipid compounds, usually named cuticular waxes, present in the cuticular layering of Quercus suber adult leaves were extracted with solvents of different polarities (n-hexane, dichloromethane and acetone) and analysed by GC–MS. Q. suber leaves have a substantial cuticular wax layer (2.8% of leaf mass and 239 g/cm2), composed predominantly by terpenes (43–63% of all compounds), followed by aliphatic long chain molecules, mainly fatty acids, and by smaller amounts of aliphatic alcohols and n-alkanes. The major identified compound was lupeol (1.2% of leaves in n-hexane extract). The recovery and composition of cuticular lipids depended on the solvent and extraction time. The non-polar or weak polar solvents n-hexane and dichloromethane extracted similar lipid yields (77% and 86% of the total extract, respectively) while acetone solubilised other cellular compounds, namely sugars, with the lipid compounds representing 43% of the total extract. For cuticular lipids extraction, solvents with a low polarity such as n-hexane are the more suitable with an adequate extraction duration, e.g., n-hexane with a minimum extraction of 3 h